IMPLEMENTASI METODE TRANSPORTASI DALAM OPTIMASI BIAYA DISTRIBUSI ROTI PADA PT. GRANEDIA MAKASSAR - Risnawati Ibnas (Teknosains, 2017)
Transportation modeling as problem solving of a good distribution from multiple sources to multiple destinations. PT. Granedia is a company of bread that distributes several types of bread production. North west corner (NWC) transportation models is the first method, and the second of method is costs optimal solution of transportation is MODI. This study aims to obtain optimal costs of transportation of PT. Gardenia with MODI method. The results indicate that the optimal transportation cost is obtained Rp. 2.432.500,-